COVID-19 pandemic impacts physical activity levels and sedentary time but not sleep quality in young badminton athletes - da Silva Santos, Arilene Maria; Rossi, Fabrício Eduardo; dos Santos Nunes de Moura, Helton Pereira; de Sousa Junior, Antonio Valdeci Marreiro; Machado, Dionis C. D.; Neves, Lucas Melo; Brito, Aldeni Silva; Moura, Pedro; Monteiro, Paula Alves; Freitas Junior, Ismael Forte [UNESP]; dos Santos, Marcos Antonio Pereira; Ribeiro, Sérgio Luiz Galan (Springer Nature, 2021)
Purpose: Regular physical activity is a good strategy to maintain the health of athletes, and prevent pain and decreased joint flexibility during the pandemic. On the other hand, higher sedentary time during the pandemic period can have deleterious effects. The objective of this study was to compare physical activity levels, sedentary time, and sleep parameters during the pre-COVID period and the COVID-19 pandemic period in young badminton athletes. Methods: Fifteen young badminton athletes were evaluated during a pre-COVID period (July 2019) and during the COVID-19 period (July 2020). Sleep parameters, physical activity level, and sedentary time were measured using a tri-axial accelerometer. Participants wore the accelerometer on their dominant wrist for 7 days consecutively. In addition, the average of each sleep parameter [time in bed and total sleep time in hours per day, sleep efficiency (%), wake after sleep onset (WASO, total per day), and sleep latency (minutes per day)] was reported over the 7-day period. Results: Athletes presented increased sedentary time (pre-COVID = 7.0 ± 1.1 vs.COVID-19 = 8.9 ± 1.9 h/day, p = 0.004, d = 1.30) and significant decreases in the total PA observed in counts per day (pre-COVID = 2,967,064.4 ± 671,544.1 vs. COVID-19 = 1,868,210.2 ± 449,768.4 counts/day, p = 0.001, d = 1.99), time in vigorous PA (pre-COVID = 7.7 ± 0.9 vs. COVID-19 = 6.1 ± 1.2 h/day, p = 0.001, d = 1.56), and time in moderate-to-vigorous PA (pre-COVID = 8.1 ± 0.9 vs. COVID-19 = 6.5 ± 1.3 h/day, p = 0.001, d = 1.48). There were no significant differences for time in light and moderate PA or in sleep parameters (p > 0.05). Conclusion: Young badminton athletes presented increased sedentary time, and decreased total physical activity, time in MVPA, and time in vigorous activities during the COVID-19 pandemic compared to the pre-COVID period, however, there were no significant differences in sleep parameters.
Keywords: Athletes; COVID-19 pandemic; Physical activity; Sedentary behavior; Sleep